Examining the Nexus: A Statistical Analysis of Factors Shaping Academic Performance - Hamza, Ali; Saddiqua, Ayesha (IJELR: International Journal of Education, Language, and Religion, 2024)
Education stands as a nation's paramount legacy, particularly to its young populace, shaping the course of a society's advancement. The quality of education a nation provides significantly dictates its progress. This study is conducted to explore the diverse factors influencing academic performance among students at Punjab University. A sample of 276 students was drawn utilizing Yamane’s formula through random sampling and data collection employed questionnaires. CGPA is used as the measure of academic performance of students. Data Analysis is done using SPSS. Results are portrayed descriptively using frequencies, percentages, and visual aids, while inferential statistics included Pearson’s Chi-Square unveil associations, Factor Analysis to extract academic factor, Mann-Whitney U and Kruskall-Wallis H tests to explore the opinions of students for different variables. Interestingly, no direct link emerged between respondents' CGPA and gender, but a notable correlation emerged between CGPA and their mothers' educational background. Via Conformity Factor Analysis four key factors surfaced: attitudes toward study, ability of time management, learning facilities and teachers’ professionalism. Mann-Whitney U test divulged differing opinions between male and female respondents concerning time management abilities and their attitudes toward studying. Additionally, Kruskall-Wallis H test highlighted varying perspectives among students of different CGPA levels regarding attitudes toward studying and teachers’ professionalism. Finding suggests that administration should not only focus on teacher trainings but also improve learning facilities.